2017
DOI: 10.1016/j.vetmic.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of CMY-2 producing E. coli in a broiler parent flock

Abstract: A B S T R A C TExtended-spectrum β-lactamase and plasmid mediated AmpC β-lactamase (ESBL/pAmpC) producing bacteria are resistant to Extended Spectrum Cephalosporins (ESC), and are present in all levels of the broiler production chain. We determined the prevalence, concentration, and persistence of ESBL/pAmpC-Escherichia coli in a broiler parent flock during the rearing and laying period. One-day old chickens were housed in four separate pens. Until week 33 no antibiotics or coccidiostatics were used. During re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 19 publications
6
36
0
3
Order By: Relevance
“…The lower prevalence of bla CTX-M with respect to bla CMY- 2 in our study in contrast to the lower prevalence of bla CMY- 2 reported in Europe (5) could be due to the presence of different plasmids containing bla CTX-M in Europe such as IncN, IncI, IncL/M and IncK (8). Nevertheless, a more recent study in Europe showed a higher proportion of bla CMY-2 (28). The difference in relative predominance of the bla CTX-M and bla CMY-2 .genes could also be explained in part by differences in geographical distribution of these genes (7).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The lower prevalence of bla CTX-M with respect to bla CMY- 2 in our study in contrast to the lower prevalence of bla CMY- 2 reported in Europe (5) could be due to the presence of different plasmids containing bla CTX-M in Europe such as IncN, IncI, IncL/M and IncK (8). Nevertheless, a more recent study in Europe showed a higher proportion of bla CMY-2 (28). The difference in relative predominance of the bla CTX-M and bla CMY-2 .genes could also be explained in part by differences in geographical distribution of these genes (7).…”
Section: Discussionmentioning
confidence: 89%
“…The presence of such plasmids in our study may explain why multidrug-resistant bacteria were selected when using lincomycin-spectinomycin at the hatchery. Studies in Japan and Netherlands also found IncA/C plasmids harboring bla CMY-2 and resistance to non β-lactam antimicrobial (28, 33). The plasmids selected in our study may have contained bla CMY-2 genes and other resistance genes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…One way to solve the problem of cross-contamination in the hatchery could be on-farm hatching. In this system, eggs are transferred from the hatchery to the farm after 18 days of incubation, which is three days before hatch (Velkers et al, 2016(Velkers et al, , 2017, thereby avoiding intense exposure of chicks to possible adverse environmental conditions (temperature, dust, fluff) in hatchers, the chick processing room, and the chick holding room (before transport) as described in in De Gouw et al, 2017. In a study by Ceccarelli et al (unpublished results) the hatchery and especially the chick processing room appeared to be a reservoir of ESBL producing E-coli bacteria.…”
Section: Introductionmentioning
confidence: 99%